Implementation Plan in Response to the Board-Endorsed Recommendations for the IEO Evaluation Report-"The IMF and Fragile States". - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2018)
This management implementation plan (MIP) proposes actions to advance the Board-endorsed recommendations of the IEO evaluation 'The IMF and Fragile States.' The actions outlined below would have resource implications. While some can be covered by reallocating resources or are already in the Work Program, others may require temporary funding; a review of staffing allocations to countries in fragile and conflict situations (FCS) might call for new permanent resources. The actions are broad in scope and self-reinforcing in effect if adopted as a package. They include: - Message of high-level commitment: Reflecting the actions of this MIP, a Management statement underscoring a strengthened institutional commitment to support FCS accompanies the MIP for Executive Board and IMFC endorsement. - An effective institutional mechanism: A high-level interdepartmental FCS Committee that reports to and seeks guidance in a formal meeting with management twice a year, will be established. The Committee will be tasked to analyze internal and external coordination issues in FCS and propose new ways tostrengthen engagement. An interdepartmental Technical Taskforce will support the Committee and report on progress in implementing this MIP, including through a Board paper on Review of FCS Engagement at end-2020. - Country engagement strategies: FCS teams will develop country engagement strategies that, drawing on relevant external expertise, will explicitly allow for thesocial and political context and the factors underpinning fragility; and lay the basis for full integration of capacity development (CD) with surveillance and lending. - Providing more sustained financial support: Staff is reviewing the lending toolkit for low-income countries to provide more tailored and flexible support, including for FCS, while ensuring uniformity of treatment. Staff will report on efforts to support FCS with protracted arrears to the Fund in the upcoming reviews of overdue financial obligations. - Practical steps to increase the impact of its CD support: Measures already in train will be complemented by the forthcoming Capacity Development (CD) Strategy Review's assessment of initiatives to better integrate CD and Surveillance, including in FCS. Staff will also review the experience with provision of statistical and financial CD in FCS. And consideration will be given to establishing a FCS multi-donor trust fund or another suitable financing vehicle to address unmet needs for long-term experts. - Human Resources (HR) issues: The forthcoming phase of the HR Strategy will look into strategic workforce and career planning, including recruitment, and will consider actions to ensure that the Fund has appropriate staff expertise and experience to work effectively in fragile states. This will include the introduction of a 'career' playbook that provides incentives for staff to be more responsive to the needs of the Fund in FCS. Adequacy of staffing allocations to FCS missions will be reviewed to ensure evenhanded treatment of the membership. Staff training on FCS will also be stepped up.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet